2017
DOI: 10.1007/s00213-017-4562-4
|View full text |Cite
|
Sign up to set email alerts
|

Locomotor activity and discriminative stimulus effects of a novel series of synthetic cathinone analogs in mice and rats

Abstract: Rationale Recent years have seen an increase in the recreational use of novel, synthetic psychoactive substances. There are little or no data on the abuse liability of many of the newer compounds. Objectives The current study investigated the discriminative stimulus and locomotor effects of a series of synthetic analogues of cathinone: alpha-PPP, alpha-PHP, alpha-PVT, 3,4-methylenedioxy-PBP (MDPBP), and ethylone. Methods Locomotor activity was assessed in an open-field assay using Swiss-Webster mice. Discr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
41
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(47 citation statements)
references
References 26 publications
6
41
0
Order By: Relevance
“…The structural similarity shared by these drugs translates into an extensive overlap in their pharmacological, neurochemical and behavioral effects. The SPCs and amphetamines share the ability to interact with monoamine transporters to cause the release of dopamine (DA), serotonin (5HT) or norepinephrine (NE) [6][7][8], alter thermoregulation [6,9,10], increase locomotor activity [6,9,11] and serve as discriminative stimuli [9,12,13]. The abuse potential of these drugs has also been affirmed in animal models of addiction [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…The structural similarity shared by these drugs translates into an extensive overlap in their pharmacological, neurochemical and behavioral effects. The SPCs and amphetamines share the ability to interact with monoamine transporters to cause the release of dopamine (DA), serotonin (5HT) or norepinephrine (NE) [6][7][8], alter thermoregulation [6,9,10], increase locomotor activity [6,9,11] and serve as discriminative stimuli [9,12,13]. The abuse potential of these drugs has also been affirmed in animal models of addiction [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5][6][7]), a growing number of synthetic cathinones have been reported to increase locomotor activity, produce cocaine-, methamphetamine-, or 3,4-methylenedioxymethamphetaminelike discriminative stimulus effects, and maintain intravenous self-administration (e.g., refs. [10][11][12][13][14][15][16][17][18][19]). For instance, we have recently shown that rats will acquire self-administration of the pyrrolidine-containing cathinones MDPV, MDPBP, MDPPP, α-PVP, and α-PPP at rates comparable to those observed with cocaine and that the potencies of these drugs to maintain responding under a fixed ratio (FR) 5 schedule of reinforcement are highly correlated with their potencies to inhibit uptake at DAT and NET but not SERT [13,16].…”
Section: Introductionmentioning
confidence: 99%
“…Preclinical studies that have examined α‐PPPs psychostimulant properties, mediated by dopaminergic signaling, employed doses similar to or higher than doses needed to abolish the DOI‐elicited HTR. For example, α‐PPP increases locomotor activity in mice with peak effects at 25 mg/kg . In rats, 30 mg/kg α‐PPP produced significant increases in locomotor activity for 60 minutes (the entire test session), while a dose of 10 mg/kg only produced significant increases for the first 50 minutes of the session .…”
Section: Resultsmentioning
confidence: 99%
“…For example, α-PPP increases locomotor activity in mice with peak effects at 25 mg/kg. 55 In rats, 30 mg/kg α-PPP produced significant increases in locomotor activity for 60 minutes (the entire test session), while a dose of 10 mg/kg only produced significant increases for the first 50 minutes of the session. 56 In another study examining the effects of pyrrolidine SCs on locomotor activity in mice, it was found that 10 mg/kg of the much more potent DAT inhibitor, α-PVP, produced significant increases in locomotor activity that lasted for 120 minutes, whereas 3 mg/kg effects lasted for 80 min.…”
Section: α-Ppps Potency To Abolish a 5-ht 2a R-mediated Behavioral mentioning
confidence: 95%